Integrating Tawhid-Based Values in Thematic Learning to Foster The Religious Character of Madrasah Ibtidaiyah Students - Ernawati, Ernawati; Ali, Mustapa; Wardi, M. Musfiatul (Jurnal Likhitaprajna, 2026)
The integration of monotheistic values into the learning process at madrasahs is important because education aims not only to develop students’ cognitive abilities but also to foster a strong religious character in their daily lives. This study aims to examine the integration of tauhid values in thematic learning and its role in shaping the religious character of students at MIN 1 Kota Mataram. This study uses a qualitative approach with a descriptive method through field research. The research subjects consisted of the principal, classroom teachers, and fifth-grade students selected using purposive sampling. Data collection was conducted through observation, interviews, and documentation, while data analysis applied the interactive model of Miles and Huberman with the support of source triangulation and techniques to ensure the validity of the findings. The results showed that the integration of tauhid values was implemented through formal thematic learning and the strengthening of the hidden curriculum. Teachers linked learning materials to moral values and tauhid, while religious habits such as Morning Qur'an, Imtak (faith and piety building), and teacher role modeling played a role in strengthening the internalization of tauhid values. The obstacles encountered included limitations in teacher competence, facilities and infrastructure, and low parental involvement. This study concludes that the successful integration of tauhid values requires ongoing collaboration between schools, families, and communities to optimize the formation of students' religious character.